ON THE ORIGINS OF DORSAL ROOT POTENTIALS - Lloyd, David P. C. (The Rockefeller University Press, 1949)
The "dorsal root potential" consists of five successive deflections designated for convenience, D.R.I, II, III, IV, and V. Of these, D.R.V alone constitutes the dorsal root potential of prior description. A study has been made of the general properties of those deflections not previously described. Dorsal root potentials are electrotonic extensions into the extramedullary root segment, the result of electrical interactions within the cord comparable to those that have been studied in peripheral nerve. Although the anatomical and electrical conditions of interaction are infinitely more complex in the cord than in nerve, it is seen that the fact of parallel distribution of primary afferent fibers pertaining to neighboring dorsal roots provides a sufficient anatomical basis for qualitative analysis in the first approximation of dorsal root potentials. An extension of the theory of interaction between neighboring nerve fibers has been made to include an especial case of interaction between fibers orientated at right angles to one another. The predictions have been tested in a nerve model and found correct. Given this elaboration, and the stated anatomical propositions, existing knowledge of interaction provides an adequate theoretical basis for an elementary understanding of dorsal root potentials. The study of general properties and the analysis of dorsal root potentials have led to the formulation of certain conclusions that follow. D.R.I, II, and III record the electrotonic spread of polarization resulting from the external field of impulses conducted in the intramedullary segment and longitudinal trajects of primary afferent fibers. D.R.IV arises in part as the result of activity in primary afferent fibers, and in part as the result of activity in secondary neurons. In either case the mode of production is the same, and the responsible agent is residual negativity in the active collaterals, or, more precisely, the external field of current flow about the collaterals during the period of residual negativity. Current flow about active primary afferent collaterals during the period of residual negativity is the agent for residual facilitation of monosynaptic reflex pathways. Since the changes in reflex threshold follow the course of residual negativity there is no need to postulate especial properties for prolonging action at regions the threshold of which is measured by means of monosynaptic test reflexes. D.R.V results from polarization of primary afferent fibers by current flow about secondary neurons. There is indication that somata rather than axons of secondary neurons generate the polarizing currents. Similarity between D.R.V and the positive intermediary potential further indicates that soma gradients established during the recovery cycle are responsible for D.R.V. Little or no net polarization of primary afferent fibers results from activity confined to the contralateral gray substance, the dorsal root potentials in contralateral recording resulting from interaction in the dorsal column or in the ipsilateral gray substance following decussation of contralaterally evoked activity. During the course of asphyxia the initial defect in reflex pathways is the failure of secondary neurons to respond to primary impulses. Subsequently block is established at the branching zone of primary afferent fibers. A relation exists between the sequence of dorsal root potentials and the cord potential sequence, the major departure from exact correspondence occurring in the region of D.R.IV and the negative intermediary potential and being of a nature to suggest that different aspects of internuncial activity are emphasized by the two methods of leading.